Quercetin exhibits multi-target anti-allergic effects in animal models: a systematic review and meta-analysis of preclinical studies - Lv, Zeyi; Pan, Zhuo; Huang, Yue; Yang, Hao; Li, Xinrong (Frontiers in Pharmacology, 2025)
BackgroundQuercetin is a naturally occurring flavonoid widely present in fruits, vegetables and tea with multiple pharmacological activities, including immunomodulatory, anti-allergic, antioxidant and anti-inflammatory properties. Preclinical studies have indicated the potential to ameliorate allergic symptoms in animal models, but comprehensive synthesis is still scarce.ObjectiveThis meta-analysis was conducted to summarize the therapeutic effects of quercetin in allergic disease models and explore its potential mechanisms.MethodsAccording to PRISMA recommendations, preclinical studies were extracted from PubMed, Web of Science and Embase databases. Thirteen eligible studies were extracted for quantitative synthesis analysis. In total, 13 studies using murine models (BALB/c, C57BL/6 mice, SKH-1 hairless mice and NC/Nga mice; Wistar and Sprague-Dawley rats) were included. The most closely related biomarkers were total IgE, OVA-specific IgE, histamine, inflammatory cytokines (IL-4, IL-5, IL-10, TNF-α, IFN-γ), and immune cell populations (macrophages, lymphocytes, eosinophils, neutrophils). Review Manager 5.4 software was used for analysis, and standardized mean differences (SMD) and 95% confidence intervals (CI) were calculated under a random-effects model.ResultsThe meta-analysis showed that quercetin significantly decreased the expression of total IgE, OVA-specific IgE, and histamine, and suppressed the infiltration of eosinophils, macrophages, and lymphocytes. Cytokine profiling showed that quercetin significantly suppressed the expression of IL-4 and TNF-α, and increased the expression of IFN-γ, which may contribute to the underlying anti-inflammatory mechanism of quercetin through Th1/Th2 immune rebalancing.ConclusionQuercetin exhibits strong anti-allergic effects in preclinical models through suppression of IgE, modulation of immune cells, regulation of cytokine network, and reduction of histamine. However, large inter-study heterogeneity and methodological limitations in original studies should be cautiously interpreted. Application in clinical settings should be carefully evaluated through well-designed trials to validate safety, efficacy, and molecular mechanisms in human populations.